Odpowiedź:
a) (6y - 2) + (3y - 2) = 6y - 2 + 3y - 2 = 9y -4
b) (6y - 2) - (3y - 2) = 6y - 2 - 3y + 2 = 9y
c) (6y - 2)(3y - 2) = 18y² -12y - 6y + 4 = 18y² - 18y + 4
d) 6x(3x - 2) = 18x² - 12x
e) -12 • 5 • 0 • (-2)= 0
f) -12 • 5 + 0 • (-2)= -60 + 0 = -60
g) -12 • 5 + 2 • (-2)= -60 - 4 = -64
h) -12 • 5 - 2 • (-2)= -60 + 4 = -56
i) [tex]8 5/6 - 4 2/5 * 1 2/3= \frac{85}{6} - 8,4 * 4 = \frac{85}{6} - 33,6 = \frac{850}{60} - \frac{2016}{60} = \frac{1166}{60}[/tex]
j)[tex]5\frac{5}{6} - 2\frac{2}{3} * 1\frac{4}{5} = 5\frac{5}{6} - 2\frac{4}{6} * 1\frac{4}{5} = 3\frac{1}{6} * 1\frac{4}{5} = \frac{19}{6} * \frac{9}{5} = \frac{171}{30} = \frac{57}{10}[/tex]